Transfer Pricing as an Instrument of Tax Avoidance in Multinational Corporations: Challenges in Law Enforcement and the Implementation of the Arm’s Length Principle in Indonesia - Sagala, Wilson; Anggusti, Martono; Sihotang, Januari (Universitas Islam Negeri Alauddin Makassar, 2026)
The development of economic globalization has encouraged increased activity of multinational companies operating across jurisdictions, thus opening up opportunities for tax avoidance practices through transfer pricing mechanisms. This practice is often used to move profits from countries with high tax rates to countries with lower tax rates, which in the end can reduce state revenues and lead to injustice in the tax system. This research aims to analyze the legal enforcement mechanism for tax avoidance practices through transfer pricing in multinational companies based on Minister of Finance Regulation Number 172 of 2023 and identify the juridical obstacles faced by the Directorate GeneralTax in its application.The research method used is normative juridical legal research with a qualitative approach through literature study of statutory regulations, legal literature and related documents. The research results show that law enforcement against transfer pricing practices in Indonesia is carried out through administrative mechanisms which include the stages of monitoring at-risk taxpayers, examining transfer pricing, determining fiscal corrections, issuing Tax Assessment Letters, as well asdispute resolution through objections and appeals to the Tax Court.Even though regulations have been updated through PMK Number 172 of 2023 by adopting the arm's length principle in accordance with international standards, its implementation still faces legal obstacles such as limitations in harmonization of domestic regulations with international standards and structural complexitymultinational company.Therefore, it is necessary to strengthen regulations and institutional capacity to increase the effectiveness of supervision and enforcement of transfer pricing laws in Indonesia.